Calculation Scheme And Mathematical Model Of Composite Roller Shaft Vibration - Abdurakhman Rafik Amonov Ogli; Axmedova Dilnoza Davlat qizi (Peerian Journals Publishing, 2024)
The article presents the calculation scheme of the pilot device of the polymer composite coating equipment on tarpaulin seams. According to the calculation scheme, a differential equation representing the vibrations of the roller was created
Keywords: Polymer; roller; seam; material